Presidential Address - NEMATODE-MICRO-ORGANISM INTERACTIONS-AN APPRAISAL - SWARUP, GOPAL (Indian Phytopathology, 2002)
I would like to take this opportunity of expressing my grateful thanks to each and every member of the Society for giving me the honour of electing me as President of thisÂ elite scientific society of the country. I am fully conscious of the responsibilities attached with the office of the President and I do hope that there has not been any cause of concern felt by the members with the present Executive. Personally, I have been very satisfied with the smooth functioning of the Society and feel proud to say that tliis is the best organised scientific society of the country.